BAKTI SOSIAL DALAM UPAYA PENCEGAHAN COVID-19 DI DESA NGIJO KECAMATAN TASIKMADU KABUPATEN KARANGANYAR - Sriyanto, Sriyanto; kasidin, Kasidin (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
Ngijo Village, one of the villages in Tasikmadu Subdistrict, Karanganyar Regency, was affected by Covid-19. Since the outbreak of Covid-19, the people's income has been reduced and even lost their livelihoods due to the production activities of the industries where they work stopped. Another factor is that the public does not fully understand Covid-19 and its prevention protocol. The Community Retrieval Activity was carried out as a form of social care at the STIE Atma Bhakti University in Surakarta through Social Service activities and outreach on prevention efforts for Covid-19. The implementation method using the counseling method and the provision of basic food packages. The implementation of the Community Retrieval Activity received a positive response from residents of Ngijo Village. Social assistance in the form of basic necessities can help alleviate the economic burden of the community, while extension activities can increase the understanding of Ngjio Village residents about Corona Virus (Covid-19), as well as prevention efforts.Â Keywords: social service, covid-19 prevention, ngijo village